Housing preference structures in East Asia: an empirical study and non-paradigmatic shifts between nearby metropoles - Zhuang, Zheng-Yun; Fu, Chen-Hua (International Journal of Strategic Property Management, 2023)
A systematic research flow was applied to the Southern Metropolis in Taiwan not only to recount residents’ considerations in this cultural area but also to compare them with those of other metropolitans on the island in relation to general housing concerns. The constructs and factors in housing decision-making were justified using the literature, confirmed with experts in the field, and organised as a decision hierarchy that formed the foundation of a survey. The investigation combined the analytic hierarchy process and Student’s t-test, both of which are credible methods, to facilitate a grounded process for mind mining. The importance of constructs/factors were thus assessed on a numerical basis, and a set of unforeseen insights were explored for the different parties of interest (e.g., buyers, construction companies, agents, asset managers, etc.). Opinion gaps between different sample groups were identified. This set of empirical knowledge filled the gap in the literature. It is noteworthy that among the constructs in the region studied, (housing) ‘conditions’ dominated ‘price’, while ‘location and transport’ was the least important. A ‘non-paradigmatic shift’ in people’s total housing preference structure, which changed gradually with decreasing population density and increasing plain geography from the north to the south between nearby metropoles, was observed, despite the niche but commensurable cultural norm in East Asia being the overall scenario of the island. Some existing claims about the housing preferences in this area were also either supported or rebutted by the quantitative evidence(s).